KONSELING ISLAMI MENGGUNAKAN KONSEP KEBAHAGIAAN AL-GHAZALI UNTUK MEREDUKSI KESEPIAN PADA KONSELI DI MTs N BANTUL KOTA YOGYAKARTA (Jurnal Pendidikan Madrasah, 2016)
This research was motivated by the chance of utilizing the scientific concept of Islam as a matter of Islamic counseling services at the school to reduce loneliness counselee who has no attachment figure. The method used in this study was twofold exploration and experimentation. This experiment uses one group pretest and posttest design, involving 8 counselee MTsN Bantul Yogyakarta. Subjects were selected based on certain criteria. Data were collected using a scale of loneliness, questionnaires, observations and interviews. Data were analyzed using Wilcoxon signed ranks test test, where the results show there is a difference between loneliness counselee before the provision of counseling services after Islami, with Z = -2.524 and p-value = 0.012 (p-value <0.050). Thus, the use of the concept of happiness counseling Islami al-Ghazali can reduce loneliness counselee.